Physiology of homeostasis and repair of skin and the role of metabolic and endrocrine factors - Costa, Rita Alves (2016)
The skin is a multifunctional organ and the primal frontier to the external environment. It is the first line of defence against external aggressors and any injuries inflicted in the vertebrate skin are rapidly repaired to re-establish immune defence and integument homeostasis. In mammals the outcome of skin injury is repair and scaring but in other vertebrates such as amphibians and fishes’ regeneration of the skin occurs and the disrupted tissue is replaced by skin of the same architecture and functionality as the original. Skin regeneration in vertebrates has been poorly explore and comparisons of the healing process in animals that heal scar free with mammalian wounds that scar will provide novel insights on the skin repair program and identify novel drug targets for mammalian skin disorders. The aim of this thesis was to identify key factors involved in skin homeostasis and repair and to generate a simple model for skin repair integrating metabolic, endocrine and immune considerations. The model species of this study was the gilthead sea bream (Sparus aurata) and using morphological and gene expression analysis the processes involved in wound healing in the regenerating fish skin in response to superficial damage caused by scale removal are described. Two gene families related to tissue repair in mammals (Angiopoietin-like family, ANGPTLs and Osteoglycin, OGN) were studied in detailed and compared and the effect of the diet supplement alpha-ketoglutarate (AKG), an inducer of collagen synthesis, in the integumentary system of adult sea bream explored. In overall the results obtained contribute to improve the current state of the art on the morphology and physiology of adult teleost skin and its regeneration after damaged and highlights for the importance of fish skin as a comparative model to study cutaneous repair in vertebrates.